Antibacterial activity of (-)-cubebin isolated from Piper cubeba and its semisynthetic derivatives against microorganisms that cause endodontic infections - Rezende,Karen C.S. (2016)
Abstract Recent publications have highlighted the numerous biological activities attributed to the lignan (-)-cubebin (1), Piper cubeba L. f., Piperaceae, and ongoing studies have focused on its structural optimization, in order to obtain derivatives with greater pharmacological potential. The aim of this study was the obtainment of (1), its semisynthetic derivatives and evaluation of antibacterial activity. The extract of the seeds of P. cubeba was chromatographed, subjected to recrystallization and was analyzed by HPLC and spectrometric techniques. It was used for the synthesis of: (-)-O-methylcubebin (2), (-)-O-benzylcubebin (3), (-)-O-acetylcubebin (4), (-)-O-(N, N-dimethylamino-ethyl)-cubebin (5), (-)-hinokinin (6) and (-)-6.6'-dinitrohinokinin (7). The evaluation of the antibacterial activity has been done by broth microdilution technique for determination of the minimum inhibitory concentration and the minimum bactericidal concentration against Porphyromonas gingivalis, Prevotella nigrescens, Actinomyces naeslundii, Bacteroides fragilis and Fusobacterium nucleatum. It was possible to make an analysis regarding the relationship between structure and antimicrobial activity of derivatives against microorganisms that cause endodontic infections. The most promising were minimum inhibitory concentration =50 µg/ml against P. gingivalis by (2) and (3), and minimum inhibitory concentration =100 µg/ml against B. fragilis by (6). Cytotoxicity assays demonstrated that (1) and its derivatives do not display toxicity.